2019
DOI: 10.31616/asj.2019.0032
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction in Spine Surgery: A Systematic Review of the Literature

Abstract: Patient satisfaction reflects the patients’ perception of the outcome of care and is being considered for use in future reimbursement schemes. No consensus exists regarding the best instrument to measure patient satisfaction in the field of spine surgery. This systematic review aimed to determine how patient satisfaction for spine surgery has been measured previously and whether a disease-specific, comprehensive instrument to measure patient satisfaction has been established; we also aimed to define the dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 84 publications
1
32
0
Order By: Relevance
“…To our knowledge, this is the first study to systematically review the available literature pertaining to spine surgery patient satisfaction as evaluated through the two most administered patient satisfaction surveys-Press Ganey and HCAHPS. Though two previous reviews have broadly reported on this topic, 13,14 this manuscript presents a comprehensive review and analysis of the two most widely utilized patient satisfaction surveys in order to identify factors most J o u r n a l P r e -p r o o f 7 predictive of patient satisfaction following spine surgery. These relatively subjective measures used to quantify patient satisfaction are increasingly being utilized in hospital systems year over year.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to systematically review the available literature pertaining to spine surgery patient satisfaction as evaluated through the two most administered patient satisfaction surveys-Press Ganey and HCAHPS. Though two previous reviews have broadly reported on this topic, 13,14 this manuscript presents a comprehensive review and analysis of the two most widely utilized patient satisfaction surveys in order to identify factors most J o u r n a l P r e -p r o o f 7 predictive of patient satisfaction following spine surgery. These relatively subjective measures used to quantify patient satisfaction are increasingly being utilized in hospital systems year over year.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that health outcomes should cover the full cycle of care and track the patient's health status after care is completed [25]. In spinal surgery, specific PROMs (e.g., of pain, such as the VAS, and of disability, such as the ODI), as well as more general PROMs such as patient satisfaction with the outcome, have been the subject of numerous studies [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]26,27]. We prospectively investigated patient-reported pain and disability levels and satisfaction in patients undergoing stabilization surgery of the thoracic and/or lumbar spine for degenerative disease, tumors, infection and traumatic or osteoporotic fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, one has to identify the factors that drive patient satisfaction first in order to improve it. It is unclear, for example, to what extent pain relief and disability improvement contribute to satisfaction after spinal surgery [2]. Psychological factors may play a role as well.…”
Section: Introductionmentioning
confidence: 99%
“…Complications with the endoscopic spinal decompression procedure requiring additional aggressive aftercare are exceedingly uncommon [57,82]. These favorable clinical outcomes assessments provided by patients were found to be reflective of their experience with anesthesia at the ASC [83]. The anesthesia requirements may vary by anterior or posterior approach, the conjunctive use of local anesthesia by the surgeon, and the surgeon's preference as to whether communication with the patient during surgery is desired.…”
Section: Discussionmentioning
confidence: 99%